Genome-wide analysis of NPR1-like genes in citrus species and expression analysis in response to citrus canker (Xanthomonas axonopodis pv. citri) - Ali, Mobeen; Shafiq, Muhammad; Haider, Muhammad Zeshan; Sami, Adnan; Alam, Pravej; Albalawi, Thamir; Kamran, Zuha; Sadiq, Saleh; Hussain, Mujahid; Shahid, Muhammad Adnan; Jeridi, Mouna; Ashraf, Ghulam Abbas; et al. (Frontiers in Plant Science, 2024)
Citrus fruits, revered for their nutritional value, face significant threats from diseases like citrus canker, particularly impacting global citrus cultivation, notably in Pakistan. This study delves into the critical role of NPR1NPR1-like genes, the true receptors for salicylic acid (SA), in the defense mechanisms of citrus against Xanthomonas axonopodis pv. citri (Xcc). By conducting a comprehensive genome-wide analysis and phylogenetic study, the evolutionary dynamics of Citrus limon genes across diverse citrus cultivars are elucidated. Through a comprehensive genome-wide analysis and phylogenetic study, we elucidate the evolutionary dynamics of NPR1like genes across diverse citrus cultivars. Structural predictions unveil conserved domains, such as the BTB domain and ankyrin repeat domains, crucial for the defense mechanism. Motif analysis identifies key elements, while cis-regulatory elements point to their roles in transcription, growth, phytohormone response, and stress. The predominantly cytoplasmic and nuclear localization of NPR1NPR1-like genes underscores their pivotal role in conferring resistance to various citrus species. Analysis of the Ks/Ka ratio indicates a purifying selection on of NPR1NPR1-like genes, emphasizing their importance in different species. Synteny and chromosomal mapping provide insights into duplication events and orthologous links among citrus species. Notably, Xac infection stimulates the expression of NPR1NPR1-like genes, revealing their responsiveness to pathogenic challenges. Interestingly, qRT-PCR profiling post-Xac infection reveals cultivar-specific alterations in expression within susceptible and resistant citrus varieties. Intriguingly, qRT-PCR profiling following Xac infection demonstrates cultivarspecific expression changes in susceptible and resistant citrus varieties. Beyond genetic factors, physiological parameters like peroxidase, total soluble protein, and secondary metabolites respond to SA-dependent PR genes, influencing plant characteristics.The nuanced interactions between defense genes (NPR1NPR1) and physiological parameters offer valuable insights into the intricate mechanisms of disease resistance. This pioneering study bridges the gap by providing the first-ever analysis of the relationship between NPR1NPR1associated genes and various physiological plant parameters in citrus cultivars susceptible and resistant to citrus bacterial canker.